Hip-hop, Identity, and Cultural Hybridity: An Exploration of Motswako as a Bicultural Phenomenon - Kgomotso Mothokhumo Ambitious Theledi; Soyiso Khetoa (E-Journal of Humanities, Arts and Social Sciences)
South Africa is a linguistically and culturally diverse country. South African locals normally assimilate more than one culture, officially and unofficially. The former refers to the systematic transition experienced by speakers of African languages in government schools from acquiring knowledge in their main language, to learning in English, while the latter refers to voluntary access to cultures of other people within their immediate environment. As locals acquire other languages, they in turn acquire the culture of the language they are acquiring because language and culture are indissoluble. This study is premised on the idea that music is a universal language with which musicians communicate aspirations, desires and experiences. Therefore, in this study, the researchers sought to explore the exchange of ideas in hip-hop collaborative projects. The study revealed that in the past, hip-hop was undesirably perceived in South Africa due to associations it had with offensive language and violence. Within the context of the historical past of South Africa, hip-hop was embraced as a mouthpiece to comment against social ills and injustices when locals could not freely express themselves. However, contemporarily, thematic concepts expressed in hip-hop include value for life, an assumption of an expensive lifestyle, objectification of females, socio-political observations, and so forth. The study concludes that collaboration is an important factor in career development within the hip-hop fraternity and encourages collaborative projects beyond terrestrial borders. This study contributes to literature on music and its impact on culture.